2023
DOI: 10.1002/chem.202203408
|View full text |Cite
|
Sign up to set email alerts
|

A Bioactive Synthetic Outer‐Core Oligosaccharide Derived from a Klebsiella pneumonia Lipopolysaccharide for Bacteria Recognition

Abstract: There is an urgent need for new treatment options for carbapenem-resistant Klebsiella pneumoniae (K. pneumoniae), which is a common cause of life-threatening hospitaland community-acquired infections. Prophylactic or therapeutic vaccination may offer an approach to control these infections, however, none has yet been approved for human use. Here, we report the chemical synthesis of an outer core tetra-and pentasaccharide derived from the lipopolysaccharide of K. pneumoniae. The oligosaccharides were equipped w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…In addition to capsule, the components of LPS have also been considered for vaccine inclusion. Conjugate vaccines linking segments of LPS (other than the O-antigen) to a protein have been described (37, 38). These vaccines elicited antibodies; however, only one group demonstrated protection from a lethal K. pneumoniae challenge.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to capsule, the components of LPS have also been considered for vaccine inclusion. Conjugate vaccines linking segments of LPS (other than the O-antigen) to a protein have been described (37, 38). These vaccines elicited antibodies; however, only one group demonstrated protection from a lethal K. pneumoniae challenge.…”
Section: Discussionmentioning
confidence: 99%
“…171 Arrays have also been used to study responses to Chlamydia pneumoniae vaccines. 154,155,173 4.1.4 Bacterial glycan-binding proteins and infectioninduced autoantibodies. Interestingly, the fimbriae of bacteria possess adhesins that enable the bacteria to bind to glycans and mediate disease.…”
Section: Antibodies To Bacterial Glycansmentioning
confidence: 99%
“…It is worth noting that the N -terminal amino acid of BSA is aspartic acid, which has a very high conversion efficiency in PLP-mediated transamination reactions . Additionally, previous research has indicated that as carrier proteins, BSA and cross-reacting material 197 (CRM197) have a similar enhancement effect on the immunogenicity of haptens . In the vaccine design, the resulting Pam 3 CSK 4 –BSA-MUC1 lipoprotein was subsequently incorporated into liposomes, which biomimics the membrane structure of tumor cells and facilitates the multivalent presentation for immune response augmentation.…”
Section: Introductionmentioning
confidence: 99%